2021
DOI: 10.1177/03080226211026557
|View full text |Cite
|
Sign up to set email alerts
|

Identifying research priorities for occupational therapy in the UK: A James Lind Alliance Priority Setting Partnership

Abstract: Introduction As the scope and nature of practice evolves in an ever-changing health and social care landscape, it is imperative the profession continues to expand the evidence base underpinning interventions. The Royal College of Occupational Therapists partnered with the James Lind Alliance to bring together people with lived experience, occupational therapists and other people working in the health and care sector to identify contemporary research priorities for the profession in the United Kingdom. Method T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…In-person meetings were not possible because of the COVID-19 pandemic; therefore, the JLA adapted its workshop delivery method to be conducted online, and learnings from other JLA PSPs were applied. 43 The steering group, with guidance from the JLA, recruited 24 youths, parents/caregivers, and clinicians from across Canada for the workshop. Workshop documentation and guidance was sent to participants 3 weeks before the workshop.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-person meetings were not possible because of the COVID-19 pandemic; therefore, the JLA adapted its workshop delivery method to be conducted online, and learnings from other JLA PSPs were applied. 43 The steering group, with guidance from the JLA, recruited 24 youths, parents/caregivers, and clinicians from across Canada for the workshop. Workshop documentation and guidance was sent to participants 3 weeks before the workshop.…”
Section: Methodsmentioning
confidence: 99%
“…Two half-day (August 18-19, 2021) virtual (Zoom Technologies Inc) workshop sessions were held to generate consensus on the top 10 unanswered questions in pediatric hospital care. In-person meetings were not possible because of the COVID-19 pandemic; therefore, the JLA adapted its workshop delivery method to be conducted online, and learnings from other JLA PSPs were applied . The steering group, with guidance from the JLA, recruited 24 youths, parents/caregivers, and clinicians from across Canada for the workshop.…”
Section: Methodsmentioning
confidence: 99%
“…Te JLA PSP in community nursing led to a wide array of unanswered evidence uncertainties in community nursing being prioritised for the frst time, using an inclusive, coproduction approach [26]. Te value of this approach is confrmed through fndings from other JLA PSPs focusing on professional groups (social workers and occupational therapists), which showed that the priorities identifed through the priority setting partnership were rarely the same as those identifed by researchers who were not involved in the process but were issues of the utmost importance to people accessing and delivering services [23,33]. Te top ten community nursing questions refect the needs, views, and priorities of community nurses, patients, and carers of diferent ages across England, across geographical regions, and take account of any diferences in perspectives according to gender and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the RCOT developed the top 10 priorities for OT research in the UK. The clinical effectiveness and cost-effectiveness of OT services are part of the research priorities (RCOT, 2021a; Watson et al, 2021). In the new Professional Standards for OT Practice, Conduct and Ethics published by the RCOT (2021b), eight outcomes are stated in Section 4.6 on Outcomes – Quality, Value and Effectiveness (see Table 1).…”
Section: Historical and Current Perspective Of Outcomes In Service De...mentioning
confidence: 99%